Proportional assist ventilation versus pressure support ventilation in the weaning of patients with acute exacerbation of chronic obstructive pulmonary disease - Anwar Ahmed Elganady; Bassem Nashaat Beshey; Amr Abdelaziz Hassan Abdelaziz (Egyptian Journal of Chest Disease and Tuberculosis, 2014)
Background: Patients with COPD are frequently hospitalized for acute exacerbations (AECOPD), which may cause respiratory failure and death. Proportional assist ventilation (PAV) is a relatively new mode of ventilator-based, inspiratory support designed to assist spontaneous breathing in patients with intact neural drive. It is a form of synchronized partial ventilatory assistance with peculiar characteristic that ventilator generates pressure in proportion to patient’s instantaneous effort. Pressure support ventilation (PSV) is an attractive weaning mode, however at higher pressure support levels, many patients displayed expiratory muscle activation indicating that the patient is “fighting the ventilator”. Objective: To compare PAV and PSV in the weaning of AECOPD patients. Patients and methods: The study was conducted on 60 patients admitted to the Department of Critical Care Medicine, at the Alexandria Main University Hospital with the diagnosis of AECOPD. Exclusion criteria included those with severe cardiac or neurological disease, and those managed by non-invasive ventilation. All patients were subjected on admission to complete history taking, complete physical examination and laboratory investigations and were treated according to guidelines of treatment of AECOPD. At the time of weaning patients were randomly categorized into two equal groups; Group A: patients weaned using PAV and Group B: patients weaned using PSV and the two groups were assessed for weaning success, patient–ventilator dys-synchrony, MV days, ICU, and hospital stay. Results: The weaning success rate was 90% in group A, and 66.7% in group B. PAV was associated with less patient–ventilator dys-synchrony and was associated with 1.5 day reduction in the mean days of mechanical ventilation, 2 day reduction in the mean days of ICU stay, and 1.8 day reduction in the mean days of hospital stay in comparison to PSV group. Conclusion: PAV was associated with less patient–ventilator dys-synchrony and associated with reduction of days of mechanical ventilation, ICU, and hospital stay.